Kepemimpinan Kolaboratif Kepala TK Bina Insan Nusantara Puloampel dalam Membangun Hubungan Antara Sekolah dengan Orang Tua - Siti Sofiyah; Mutoharoh Mutoharoh; Andriyani Sariwardani (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the implementation of collaborative leadership by the principal of TK Bina Insan Nusantara Puloampel in fostering a harmonious relationship with students’ parents. The research employed a descriptive qualitative approach with subjects including the principal, teachers, and parents. Data were collected through in-depth interviews, participatory observation, and document analysis, then analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that the principal actively involves parents in various activities and decision-making related to children's education, resulting in open and mutually supportive two-way communication. Teachers act as mediators strengthening the synergy between the school and parents. Policies and programs supporting collaboration, such as regular parent meetings and parenting workshops, also contribute to creating a conducive and inclusive learning environment. This study confirms that the applied collaborative leadership enhances the quality of school-parent relationships and supports the optimal development of early childhood